Ketahanan Pangan Tingkat Rumah Tangga Perkotaan Dan Pedesaan Di Kabupaten Kutai Kartanegara - Sari, Nilam Anggar (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2017)
Since household food security is one of the goals of economic, social and cultural development programs in Kutai Kartanegara, it is important to estimate the level of household food security. This estimation is done through various indices such as Aggregate Household Food Security Index (AHFSI). This index was first proposed by the FAO. Using this index, the present article tries to estimate the level of household food security in district Kutai Kartanegara 2015 are differentiated by urban and rural. The magnitude of the AHFSI index for 2015 is 65.67, where in urban areas it reaches 65.17 and in rural areas reaches 65.94. This means that in terms of household energy consumption on average, household food security within and relatively not much different. Since AHFSI is between 65 - 75, households in Kutai Kartanegara are on average included in the low AHFSI category, both in urban and rural areas. Households in Kutai Kartanegara in 2015 are categorized as follows: 48.59 percent are food-resistant households, 18.49 percent of vulnerable households, 1.28 percent of poor households, and 15.64 percent of food insecurity households with access to both physical and low economic access to adequate food. Percentage of food insecure households in urban areas that is more food resistant than rural areas. This is because households in urban areas have relatively good physical access and economic access compared to rural households. Keywords: Household Food Security, AHFSI, Urban, Rural